2017
DOI: 10.1038/s41598-017-04526-7
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor 1 in relation to future hearing impairment: findings from the English Longitudinal Study of Ageing

Abstract: Insulin-like Growth Factor 1 (IGF-1) is associated with cardiovascular disease, itself a risk factor for hearing impairment, and, in animal studiesafter adjustment for a range of potential confounders. Among people ≥60 y (n = 2990) there was a nonsignificant 'J'-shaped association. Our observational evidence that higher levels of IGF-1 appeared to confer some protection against hearing impairment in some older adults warrants replication in other prospective cohort studies.Age-related hearing loss (presbycusis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…Achieving an age of 58 to 73 years, the age of their participants, without other exposures known to increase risk of hearing loss may indicate that these participants represent a very different group from the EHLS and the U.S. population in general. The findings of Lassale et al 18 were for a specific age group in their population, and these results similarly may not be applicable to the general population. In the present study, in a similar age group of 53 to 59 years, a relationship between IGF1 and hearing was not observed.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…Achieving an age of 58 to 73 years, the age of their participants, without other exposures known to increase risk of hearing loss may indicate that these participants represent a very different group from the EHLS and the U.S. population in general. The findings of Lassale et al 18 were for a specific age group in their population, and these results similarly may not be applicable to the general population. In the present study, in a similar age group of 53 to 59 years, a relationship between IGF1 and hearing was not observed.…”
Section: Discussionmentioning
confidence: 65%
“…In previous studies, higher serum aldosterone was shown to have a cross‐sectional relationship to lower hearing thresholds, better performance on HINTs, and was protective in animal models . Higher levels of IGF1 were shown to decrease incident HI among those 50 to 60 years of age in a longitudinal cohort, and low levels proved detrimental to hearing in animal models . BDNF has been suggested as a possible treatment for deafness and was effective in treatment of ototoxic and noise‐induced deafness in animal models .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations